Use of Modern Digital Technologies in Managing the Information Support Processes of Banks’ Economic Security - BondarukТ. Н. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article provides a comprehensive analysis of the impact of modern digital technologies on the transformation of information support systems for banks’ economic security in the context of the rapidly developing digital economy and the growing intensity of financial, cyber, and operational risks. It is argued that digitalization in the banking sector goes beyond the technological upgrade of IT infrastructures and creates prerequisites for revisiting the conceptual foundations of risk modelling, information flow management, and organizational decision-making practices. The study identifies Big Data technologies, artificial intelligence, machine learning, cloud computing, open banking, remote identification, and cybersecurity systems as the key drivers of modernization of banks’ information and analytical subsystems. The research systematizes contemporary approaches to interpreting digital transformation and highlights their significance for building a new model of information and analytical activity aimed at proactive threat detection and anticipatory responses to external changes. Digital technologies expand data sources, ensure integration of internal and external information flows, improve the precision of predictive analytics, and significantly shorten decision-making time. Particular attention is paid to the role of artificial intelligence in behavioural analytics, early-warning risk systems, and automated transaction monitoring mechanisms. An organizational and functional model for managing information processes of economic security is proposed, encompassing data formation, integration, storage, analysis, and protection blocks. The study demonstrates that implementing such a model enables the formation of a closed-loop information cycle “data – analytics – decisions – protection – new data”. Strengthening this model technologically and institutionally enhances banks’ adaptability to external shocks, minimizes information asymmetry, expands risk-control capabilities, and reinforces financial resilience.